2015
DOI: 10.5039/agraria.v10i3a4546
|View full text |Cite
|
Sign up to set email alerts
|

Biochar, farmyard manure and poultry litter on chemical attributes of a Distrophic Cambissol and soybean crop

Abstract: The use of organic wastes, as an alternative to inorganic fertilizer, can be an important strategy for Brazilian agriculture. The objective was to evaluate the residual effects and the agronomic efficiency of organic amendments use on chemical attributes of a Haplic Cambisol and to soybean crop. A field experiment was carried out in a completely randomized split-plot design with three replications in Minas Gerais, Brazil, 2008/09. In the plots, the sources of organic amendments were evaluated (poultry litter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(24 reference statements)
1
1
0
1
Order By: Relevance
“…According to the fitted Gaussian linear spatial model (GSLM), the value associated with the potassium content (K) ( Table 3) was the highest and presented a positive sign, indicating that it was the covariate that contributed the most to an increase in the average of the soybean yield (t ha -1 ). This result corroborates with the study of Dos Passos et al (2015), considering that this nutrient is the second most absorbed by the soybean plant, being essential for the growth and development of the plants (Li et al, 2015). The estimates of the parameters associated to the covariates of phosphorus (P) and manganese (Mn) contents indicated that these covariates contributed little to the estimated soybean yield ( Table 3).…”
Section: Resultssupporting
confidence: 88%
“…According to the fitted Gaussian linear spatial model (GSLM), the value associated with the potassium content (K) ( Table 3) was the highest and presented a positive sign, indicating that it was the covariate that contributed the most to an increase in the average of the soybean yield (t ha -1 ). This result corroborates with the study of Dos Passos et al (2015), considering that this nutrient is the second most absorbed by the soybean plant, being essential for the growth and development of the plants (Li et al, 2015). The estimates of the parameters associated to the covariates of phosphorus (P) and manganese (Mn) contents indicated that these covariates contributed little to the estimated soybean yield ( Table 3).…”
Section: Resultssupporting
confidence: 88%
“…Neste contexto, a utilização de resíduos orgânicos, advindos da própria propriedade rural, como fonte alternativa ao fertilizante inorgânico é uma importante estratégia para a agricultura brasileira, principalmente para a agricultura familiar (PASSOS et al, 2015). Além disso, a utilização do solo em cultivo intensivo pode provocar o esgotamento dos nutrientes e, para superar a rápida diminuição da fertilidade do solo, os insumos orgânicos são aplicados para melhorar e manter sua fertilidade (NDUBUISI-NNAJI et al, 2011).…”
Section: Introductionunclassified
“…Another issue that may be related to pH is the low value of the β 1 coefficient, since soil acidity decreases release of available P in organic matter of the soil (Santos et al, 2013;Passos et al, 2015).…”
Section: Resultsmentioning
confidence: 99%